VALIDITAS MODUL DIGITAL BERBASIS CANVA PADA PLATFORM HEYZINE FLIPBOOK DENGAN PENDEKATAN DEEP LEARNING MATERI SUMBER ENERGI KELAS III SD - Ester Sinurat; Faizal Chan; Khoirunnisa Khoirunnisa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Science learning at the elementary school level requires the availability of teaching materials that are able to present concepts concretely, contextually, and in line with the developmental stages of students' learning. However, the teaching materials used in third-grade science learning are still dominated by printed modules that tend to be textual and lack interactivity, so they do not fully support conceptual understanding, especially in the material on energy sources. This research is directed at developing and assessing the feasibility of a Canva-based digital module published through the Heyzine Flipbook platform by integrating a deep learning approach in third-grade science learning in elementary school. The method applied is Research and Development (R&D) with the ADDIE model that includes the stages of analysis, design, development, implementation, and evaluation, but the implementation of the research is limited to the development stage because the focus of the study is on testing the validity of the product. The digital module was designed using the Canva application and presented in the form of an interactive digital book through the Heyzine Flipbook platform. The product assessment stage involved three experts, namely a material expert, a language expert, and a media expert, with a five-level Likert scale questionnaire instrument. The data obtained were analyzed using a percentage technique to determine the level of module validity. The results of the study indicate that the digital module is categorized as very valid in all assessment aspects, including the feasibility of the material, language, and media, with an average validity level of 95.44%. Therefore, the resulting digital module is considered suitable for use as a science and science teaching material on energy sources for third-grade elementary school students. However, this study has not included practicality and effectiveness tests, so further research is needed to examine its application in classroom learning. ABSTRAKPembelajaran IPAS pada jenjang sekolah dasar menuntut ketersediaan bahan ajar yang mampu menyajikan konsep secara konkret, kontekstual, serta selaras dengan tahap perkembangan belajar peserta didik. Namun, bahan ajar yang digunakan pada pembelajaran IPAS kelas III masih didominasi oleh modul cetak yang cenderung bersifat tekstual dan minim interaktivitas, sehingga belum sepenuhnya mendukung pemahaman konsep, khususnya pada materi sumber energi. Penelitian ini diarahkan untuk mengembangkan sekaligus menilai tingkat kelayakan modul digital berbasis Canva yang dipublikasikan melalui platform Heyzine Flipbook dengan mengintegrasikan pendekatan deep learning dalam pembelajaran IPAS kelas III sekolah dasar. Metode yang diterapkan adalah Research and Development (R&D) dengan model ADDIE yang mencakup tahapan analysis, design, development, implementation, dan evaluation, namun pelaksanaan penelitian dibatasi hingga tahap development karena fokus kajian berada pada pengujian validitas produk. Modul digital dirancang menggunakan aplikasi Canva dan disajikan dalam bentuk buku digital interaktif melalui platform Heyzine Flipbook. Tahap penilaian produk melibatkan tiga pakar, yaitu ahli materi, ahli bahasa, dan ahli media, dengan instrumen angket skala Likert lima tingkat. Data yang diperoleh dianalisis menggunakan teknik persentase untuk mengetahui tingkat validitas modul. Hasil penelitian menunjukkan bahwa modul digital berada pada kategori sangat valid pada seluruh aspek penilaian, meliputi kelayakan materi, kebahasaan, dan media, dengan rata-rata tingkat kevalidan sebesar 95,44%. Oleh karena itu, modul digital yang dihasilkan dinilai layak dimanfaatkan sebagai bahan ajar IPAS materi sumber energi bagi peserta didik kelas III sekolah dasar. Meskipun demikian, penelitian ini belum mencakup uji kepraktisan dan efektivitas sehingga diperlukan penelitian lanjutan untuk mengkaji penerapannya dalam pembelajaran di kelas.